A multi-center, randomized, double-blinded, parallel, placebo-controlled study to assess the efficacy and safety of Shenqisuxin granule in complex coronary artery disease after PCI: Study protocol - Wu, Xiaoping; Yan, Mingyu; Pang, Xingxue; Wu, Hui; Hu, Zhigeng; Xiao, Rui; Pan, Jianlue; Li, Ying; Shi, Shengnan; Deng, Yanping; Li, Jiaxi; Wang, Peili; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction The Shenqisuxin granule (SQSX), a novel Chinese herbal formula, has the effect of preventing in-stent restenosis and improving angiogenesis. We intend to evaluate the efficacy and safety of SQSX to provide a possible therapeutic strategy for complex coronary artery disease (CCAD) after percutaneous coronary intervention (PCI). Methods/design The study is a multi-center, randomized, double-blinded, parallel, placebo-controlled trial. A total of 120 participants will be randomized 1:1 into the intervention group and the control group. Based on standardized treatment, the intervention group and control group will receive SQSX and placebo for 2 months, respectively. The primary outcomes, metabolic equivalents (METS) and peak oxygen uptake (Peak VO2), and the secondary outcomes, including other indicators of cardiorespiratory fitness (CRF), the European Quality of Life Questionnaire (EQ-5D-5L), the Seattle Angina Scale (SAQ), etc., will be assessed at baseline and 2 months ± 3 days. In addition, the survey scales will also be tested at 1 month ± 3 days. Trimethylamine N-oxide (TMAO), high-sensitivity C-reactive protein (hs-CRP), and gut microbiota features will be assessed at baseline and 2 months ± 3 days to probe possible mechanism. The major adverse cardiac and cerebrovascular events (MACCE) and bleeding events will be monitored until the 12-month follow-up. Discussion This study is launched to assess the efficacy and safety of SQSX in CCAD after PCI and probe the possible mechanism. Clinical trial registration China Clinical Trial Registry, ChiCTR2200060979, Registered on June 14, 2022.